Peer-assisted learning - Mona G. Amer; Raad M. M. Althaqafi; Sara A.; Atheer Alsufyani; Faisal S. Alrubaei; Nader M. Mohamed (Instituto Politécnico de Viseu, 2021)
Introduction: Peer-assisted learning (PAL) is a teaching method that develops new knowledge and skills through active learning support from peers. Objectives: To assess the impact of PAL in medical education, by collecting quantitative data that explore its effectiveness. To evaluate students' perception of and satisfaction with PAL. Methods: A 5-point Likert scale survey was developed for students participating in the PAL program either as tutors or learners. Data were compared and statistically analyzed according to gender, GPA, and year of study. Moreover, follow up of peer tutors and peer learner's achievement was done through comparing their grades with those that not shared in PAL and with their GPA of previous year. Results: Statistical analysis of questionnaire data revealed that medical students regarded voluntary peer-teaching similarly to faculty teaching and have a generally positive perception of PAL. Most of the respondents reported that they benefited both professionally and personally from PAL activities. They recommended expanding the role of PAL and officially incorporating PAL sessions into the curriculum. Students' achievement was significantly increased for those who acted as peer learners and peer tutors. Conclusions: Using PAL in conjunction with other teaching and learning methods provides additional value by fostering cooperation and social interaction among medical students and further prepares them for their future role as medical science educators. Additional research into the impact of PAL on academic achievement, both short- and long-term learning outcomes, in medical programs is warranted.